Effect of Timber Type and Nail Spacing on the Hysteretic Behavior of Timber-Framed Shear Walls with Openings - Döngel, Ni̇hat; Söğütlü, Cevdet; Isleyen, Ummu Karagoz; Toğay, Abdullah; Anil, Özgür (Springer Science and Business Media LLC, 2017)
In scope of the study, behavior of timber-framed shear walls having openings with variable dimensions and locations subjected to reverse cyclic loading is experimentally investigated. Main variables considered in the study are the aspect ratios of timber-framed panel walls, dimensions and locations of the openings on the panel walls, material of the timber frames and spacings of the nails used in the panel connections. Load–displacement relationships, strengths, stiffnesses, displacement ductility ratios, energy dissipation capacities and failure mechanisms of the specimens are determined. The ultimate load capacities of the timber-framed panels are calculated as per Eurocode 5 and presented in comparison to experimental results. Moreover, lateral load-resisting capacities and load–displacement relationships of the test specimens are numerically calculated with finite element analyses. A good agreement was observed between the numerical and experimental results. From the test results, it is observed that the load behavior relationships of the test specimens significantly affected by aspect ratios, location of the openings, material of the timber frames and spacing of the nails used to provide connection between the timber-framed panel elements. Also, the increasing size of the openings decreased the stiffness’ of the test specimens.